Comparative Scenario between Grid and Grid based Cluster network in Wireless Sensor Network (International Journal of Engineering and Computer Science, 2015)
- Wireless Sensor Network composed of a set of tiny sensor nodes. The nodes are continuously sense and transmit the data. WSN have a wireless nature, due to this has a limited lifetime. So increase the lifetime of Wireless Sensor Network and Minimize energy cost in wireless sensor network are an important problem. To solve this problem different technique are always used, among the entire technique grid network and grid based clustering network are more efficient. In this paper we compare A Grid network with Grid based cluster network to provide a comparison results based on less energy consumption. We are working on QualNet tools to simulate the scenarios.